Encapsulated peritoneal sclerosis - Hira Asghar; Rabail Raza; Imran Khalid Niazi; Kashif Siddiqui (Journal of the Pakistan Medical Association, 2022)
Encapsulating peritoneal sclerosis (EPS) also known as abdominal cacoon is a rare cause of acute or subacute small bowel obstruction. It is characterized by total or partial encasement of the small bowel within a thick fibrocollagenous membrane which may be formed in response to prolonged, repetitive, and severe insult to the peritoneal mesothelium. This is frequently seen in the setting of peritoneal dialysis. However other causes may include chronic inflammation. We present a case of EPS in a male with infrequent abdominal pain, nausea and fever.... Continue